ANALISIS GENRE HORROR PADA FILM HEREDITARY (2018) DAN MIDSOMMAR (2019) (The Commercium, 2022)
The research conducted is an analysis of the Horror genre films entitled Hereditary (2018) and Midsommar (2019). The approach used for this research is a qualitative approach, which focuses on analyzing genre characteristics to examine data on a media using a schema of the basic genre repertoire of elements of Nick Lacey's to describe the character of the film genre. Hereditary and Midsommar films have the characteristics of the dominant Occult Horror genre and strong neo-paganism. The results of this study found a pattern in the Occult Horror genre that prioritizes the side of the neopagan group which can be seen based on showing certain symbols and ceremonies that involve human sacrifice explicitly through narration, characters, setting or background, iconography, and style or format. The literature review that researchers used in this study included film texts and genres, genre theory, occult horror genre films, Hereditary and Midsommar films. From the analysis carried out by the researchers, it was found that scenes that can cause horror about unusual things, the supernatural including religious groups are the main things in these two films. Both films have won multiple awards for their disturbing and disgusting narratives and plots, explicit scenes of sadistic murder and how disturbed mental health can lead to a series of problems. Keywords: film, genre analysis, mass media, horror, cult ritual